Formulation and Optimization of Candesartan Cilexetil Nano Lipid Carrier: In Vitro and In Vivo Evaluation - Paudel, Anjan; Ameeduzzafar; Imam, Syed S.; Fazil, Mohd; Khan, Shahroz; Hafeez, Abdul; Ahmad, Farhan Jalees; Ali, Asgar (Current Drug Delivery, 2017)
Purpose: The objective of this study was to formulate and optimize Candesartan Cilexetil (CC) loaded nanostructured lipid carriers (NLCs) for enhanced oral bioavailability. Method: Glycerol monostearate (GMS), Oleic acid, Tween 80 and Span 40 were selected as a solid lipid, liquid lipid, surfactant and co- surfactant, respectively. The CC-NLCs were prepared by hot emulsion probe sonication technique and optimized using experimental design approach. The formulated CC-NLCs were evaluated for various physicochemical parameters and further optimized formulation (CC-NLC-Opt) was assessed for in vivo pharmacokinetic and pharmacodynamic activity. Results: The optimized formulation (CC-NLC-Opt) showed particle size (183.5±5.89nm), PDI (0.228±0.13), zeta potential (-28.2±0.99mV), and entrapment efficiency (88.9±3.69%). The comparative in vitro release study revealed that CC-NLC-Opt showed significantly better (p<0.05) release and enhanced permeation as compared to CC-suspension. The in vivo pharmacokinetic study gave many folds increase in oral bioavailability than CC suspension, which was further confirmed by antihypertensive activity in a murine model. Conclusion: Thus, the results of ex vivo permeation, pharmacokinetic study and pharmacodynamics study suggest the potential of CC-NLCs for improved oral delivery.
Keywords: bioavailability study